How Effective is the Tobin Tax in Coping with Financial Volatility? - (:unkn) unknown (My University, 2006)
The last two decades have witnessed increasingly frequent and severe financial crises that many related to short-term speculation. Consequently, James Tobin's proposition of a small tax on cross-border currency transactions to reduce such speculation has featured prominently in the discussions on the future of the international financial system. Opponents claim that such a tax can easily be circumvented and would not be effective. This paper scrutinizes these claims in the light of recent refinements made in the literature to make an assessment for the Tobin tax's effectiveness in coping with financial volatility. Evaluation of the paper suggests that such a tax, indeed, would not only be effective in reducing financial volatility but also technically feasible and relatively easy to apply.

Son yirmi yılda çoğu gözlemcinin kısa vadeli spekülasyonla ilişkilendirdiği, giderek artan sıklık ve şiddette mali krizlerle karşı karşıya kalınmıştır. Bu durum, kısa vadeli spekülasyonları azaltmak için James Tobin 'in döviz işlemleri üzerinden ufak bir vergi alınması şeklindeki önerisinin, uluslararası mali sistemin gelecekteki yapısını şekillendirme tartışmalarında ağırlık kazanmasına yol açmıştır. Karşıtları, böyle bir vergiden kolayca kaçınılabileceği ve sonuçta verginin etkin olmayacağı iddiasındadırlar. Bu makale, Tobin vergisinin mali oynaklığı (volatility) azaltmadaki etkinliğine ilişkin söz konusu iddiaları literatürdeki gelişmeler ışığında irdelemektedir. Makaledeki değerlendirmeler, böyle bir verginin sadece mali oynaklığı azaltmada etkin olmadığı, aynı zamanda teknik olarak uygulanmasının olanaklı ve oldukça kolay olduğunu ortaya koymaktadır.
Tobin Vergisi Mali Oynaklığı Azaltmada Ne Kadar Etkindir?